Hospital to home transport at end of life: Survey of clinician experience. (March 2020) - Raed, Mona; Grossoehme, Daniel H; Brown, Miraides; Friebert, Sarah
Background: Palliative transport is transport home of patients requiring critical care transport support with expectation of imminent death. Many parents prefer their child's death at home; evidence suggests death in the preferred location improves bereavement outcomes. Little is known about the clinical and demographic diversity of patients receiving palliative transport or the perspectives of participating staff. Aim: The objectives of the present study were to (1) characterize demographic and clinical factors involved in palliative transport, (2) identify challenges encountered, and and (3) ascertain staff perspectives. Design: Ten-year retrospective chart review and cross-sectional staff survey using study-specific questionnaire. Setting/participants: Twenty-three patients had palliative transport from a tertiary pediatric hospital from 2004 to 2013, of which 12 met inclusion criteria. Survey responses from 22 participating staff were received. Results: The cohort of 12 patients was 58% female, with a mean (range) age of 5.5 (0.01–22) years; racial composition was not significantly different than the palliative care clinical census over the same time period. Distances under 30 miles accounted for 50% of palliative transports. The majority of patients (75%) died within 2 days of palliative transport. Six unanticipated events are described. Staff reported palliative transport as a positive experience, regarding it as an important job component. However, 63% were dissatisfied or undecided about the plan should the patient die enroute, and 48% experienced some level of dissatisfaction with communication. Conclusion: Palliative transport is a feasible option for some patients. Staff experienced palliative transport as valuable, although process concerns were noted. This study underscores the importance of preparedness, training, and education for palliative transports.